2017
DOI: 10.1177/0890334416685072
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial on Effect of Intermittent Early Versus Late Kangaroo Mother Care on Human Milk Feeding in Low-Birth-Weight Neonates

Abstract: Early KMC significantly increased exclusive human milk feeding and direct breastfeeding in LBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 22 publications
0
37
0
4
Order By: Relevance
“…Furthermore, this study in accordance with the previous study from Jayaraman et al, who demonstrated that the frequency of apnea and recurrent apnea was significantly reduced in the early KMC infants, compared with late KMC infants (11.9 vs. 20%, p ¼ 0.027 vs. 8.8 vs. 15%, p ¼ 0.02) in a randomized controlled trial. 16 However, the practical significance of six times less apnea during a whole hospital stay found in the current study may be limited in a clinical setting.…”
Section: Univariate Analysis For the Potential Confounding Variablesmentioning
confidence: 68%
“…Furthermore, this study in accordance with the previous study from Jayaraman et al, who demonstrated that the frequency of apnea and recurrent apnea was significantly reduced in the early KMC infants, compared with late KMC infants (11.9 vs. 20%, p ¼ 0.027 vs. 8.8 vs. 15%, p ¼ 0.02) in a randomized controlled trial. 16 However, the practical significance of six times less apnea during a whole hospital stay found in the current study may be limited in a clinical setting.…”
Section: Univariate Analysis For the Potential Confounding Variablesmentioning
confidence: 68%
“…Advising mothers of hospitalized newborns increases the incidence of initiation of breastfeeding and the extraction of human milk without increasing maternal stress and anxiety. Early Kangaroo mother significantly increased exclusive breastfeeding and direct breastfeeding in very low birth weight infants [21].…”
Section: Resultsmentioning
confidence: 94%
“…Similar presentation of high frequency of male babies was noted in other studies. 18,19 The mean gestational age of the mothers in case and control was 34.1±2.3 and 33.2±2.12 weeks respectively. Similar significance was found in the study done by Gathwala G et al 19 The mean age of the mothers in case and control group was 24.2 and 22.5 years respectively.…”
Section: Discussionmentioning
confidence: 99%